2014
DOI: 10.1039/c4gc00543k
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable polyacetals from isohexides

Abstract: A single step synthetic protocol to access a small family of renewable diacetals was established. The resultant chiral diacetals are valuable building blocks in pharmaceuticals and materials science. To demonstrate their synthetic competence, isohexide-diacetals (2a-c) were subjected to acetal metathesis polymerization and the corresponding polymers (poly2a-c) were isolated as white solids with molecular weights in the range 3200-27 600 (g mol −1 ). The semi-crystalline polymers displayed glass transition temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 34 publications
(15 reference statements)
1
29
0
Order By: Relevance
“…polymers with spirocyclic units in the main chain [1][2][3][4][5][6][7]. This cyclic structure restricts conformational flexibility and hence results in an increased thermal stability of the polymers.…”
Section: Introductionmentioning
confidence: 99%
“…polymers with spirocyclic units in the main chain [1][2][3][4][5][6][7]. This cyclic structure restricts conformational flexibility and hence results in an increased thermal stability of the polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, significant progress has been made in the synthesis of polymers derived from isohexides; however, degradation of these polymers remains uninvestigated. In our pursuit to address these two issues of reactivity of the isohexides and degradation of the resultant polymers, this group recently reported syntheses of isohexide‐diacetals and their corresponding polyacetals . We also demonstrated that the isohexide derived polyacetals degraded under slightly acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Even partial replacement of petroleum‐based raw materials by renewable resources is a major contemporary challenge in terms of both economic and environmental aspects . In this context, there has been significant contributions from the scientific community, and various renewable resources have been identified . Several renewable products have been successfully launched such as sugar cane based polyethylene, poly‐lactic acid (PLA), and polyhydroxyalkanoates, to name a few .…”
Section: Introductionmentioning
confidence: 99%